(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Perinatal mental disorders (PMDs) are the most common complication of pregnancy and the first postpartum year. Since PMD prevalence and use of mental-health services by perinatal women in Switzerland are unknown, we analysed existing health statistics. METHODS We used statistics from a large health insurance company, hospitals and freelance midwives. We assessed the annual rates of mental healthcare use in perinatal women (n = 13 969). We ascertained the annual rates of PMD treatment in obstetric inpatients (n = 89 699), and annual rates of PMD records by freelance midwives (n = 57 951). In 15 104 women who gave birth in 2012 or 2013, we assessed use of mental-healthcare before and during pregnancy, and in the postpartum year. For the same sample, we determined proportions of medication and consultation treatments. We used multiple regression analysis to estimate the influence of PMD on overall healthcare costs of mandatory health insurance. RESULTS The annual rate of mental-healthcare use by perinatal women was 16.7%. The annual rate of PMD treatment in obstetric inpatients was 1.1%. The annual rate of PMD records in the midwifery care setting was 2.9%. Women with PMD use mental health services mainly in non-obstetric outpatient settings. Medication was the most frequent treatment. Primary care providers and mental health specialists contributed almost equally to consultation treatments. PMD during pregnancy raised overall costs of healthcare in the postpartum year by 1214 Swiss francs. ​ CONCLUSIONS: Health-system research and perinatal healthcare should take into consideration the high prevalence of PMD. Real PMD prevalence may be even higher than our data suggest and could be assessed with a survey using our model of PMD prevalence.